STUDY OF THE AVAILABILITY OF FODDER AND PALM LEAVES ON THE NEED FOR GOAT FEED IN NAGAN RAYA REGENCY - Devi Agustia; Yoga Nugroho; Dedy Darmansyah; Abdillah Rasyid (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Oil palm fronds are waste from the harvesting process that is routinely carried out by oil palm plantation business actors. Oil palm fronds can be obtained throughout the year along with harvesting fresh fruit bunches.Based on availabilitycontinuously, palm fronds can be used as processed products, one of which is as an alternative feed for ruminants as a substitute for grass so that it can be used as animal feed.The purpose of this study was to determine the potential of palm fronds and leaves as goat feed in Nagan Raya district. This research was conducted in Nagan Raya Regency in several stages, namely demand and availability, internal and external conditions. Based on the results of the study it can be seen that the average feed requirement per 1 year old goat ready for slaughter in Nagan Raya Regency is around 990 kg. In a month, goats need as much as 90 kg of feed with a composition that is usually done by goat breeders as much as 40% grass and 60% palm fronds and leaves so that in 1 Ha of Oil Palm Plantation it can meet <52 goats (composition of 60% Palm feed = 54 kg , 40% grass feed = 36 kg). It can be seen that the development of goat farming will be influenced by various conditions, namely internal and external. This condition can be seen by using a SWOT analysis to find out what are the strengths, weaknesses, opportunities, and threats for farmers. External conditions on goat farms are everything that is outside of the condition of the livestock that can affect the sustainability of the livestock business.